Foundation Flash CS5 for Designers - Green, Tom.; Dias, Tiago; SpringerLink (Online service) (Berkeley, CA : Apress, 2010)
Flash is one of the most engaging, innovative, and versatile technologies available$1 (Ballowing the creation of anything from animated banners and simple cartoons to rich Internet applications, interactive videos, and dynamic user interfaces for web sites, kiosks, devices, or DVDs. The possibilities are endless, and now it just got better. Flash CS5 boasts a host of new features, including better support for mobile devices, a whole new animation engine enabling full manipulation of tweens and paths, custom easing, improved inverse kinematics, a revamped timeline, built-in 3D, and much more. This book is all you$1 (Bll need to learn Flash CS5 from the ground up. If you already have Flash experience, this book will allow you to quickly catch up on all the cool new features. Flash experts Tom Green and Tiago Dias guide you step-by-step through all facets of Flash CS5, keeping the emphasis firmly on good design techniques that you use in your own projects. Learn Flash design from the ground up, or just get to grips with the new features, with a series of step-by-step tutorials. Provides an easy introduction to ActionScript 3.0 coding, but the focus is mainly kept on design. Learn from the experts$1 (Bwritten by renowned Flash designers Tom Green and Tiago Dias.s
Learning the Flash CS5 Professional Interface -- Graphics in Flash CS5 -- Symbols and Libraries -- ActionScript Basics -- Audio in Flash CS5 -- Text -- Animation, Part 1 -- Animation, Part 2 -- Flash Has a Third Dimension -- Video -- Building Interfaces with the UI Components -- XML (Dynamic Data) -- CSS -- Building Stuff -- Optimizing and Publishing Flash Movies.
Keywords: Computer science; Computer graphics; Computer Science; Computer Graphics